RETROSPECTIVE STUDY ON THE COMPARISON OF OUT-OF-HOSPITAL AND IN -HOSPITAL SUDDEN CARDIOVASCULAR DEATH: AN ITALIAN EXPERIENCE. - Giovanni Bartoloni (Euromediterranean Biomedical Journal, 2015)
A retrospective study of forensic autopsies was carried out in the time interval January 2007 to December 2012 at the Forensic Pathology Service, Catania, south Italy, with a reference population of 3 000 000 inhabitants. During the study period, 1346 forensic autopsies were performed, including 223 (16.57%) sudden/unexpected deaths. Among the latter, 116 fulfilled the criteria of out-of-hospital (Group A) and 107 were in-hospital (Group B) sudden/unexpected deaths with suspected medical malpractice and/or a professional liability claim. In Group A, coronary artery disease was the most common cause of death (N=67; 57.65 %), followed by cardiomyopathies (N=19, 16.38%) and myocarditis (N= 6; 17%). In Group B, coronary artery disease (N=32, 29.91%), post-procedural or postsurgical complications (N=30, 28.04%), pulmonary thromboembolism (N= 17; 15.89%) and aortic dissection (N=7, 6.54%) were the main causes of death.